Identification and mechanistic analysis of neurovascular coupling related biomarkers for diabetic macular edema - Chen, Tianpeng; Sheng, Shufan; Chen, Jing; Wang, Xiaole; Shang, Yanxing; Duan, Chengwei; Liang, Caixia; Song, Yu; Zhang, Dongmei (Frontiers in Molecular Biosciences, 2024)
Introduction Diabetic macular edema (DME) is a major cause of vision loss in the sick with diabetic retinopathy. The occurrence of DME is closely related to the breakdown of neurovascular coupling; however, its underlying mechanism has not been fully elucidated. The aim of this study was to investigate the diagnostic biomarkers and potential molecular mechanisms associated with neurovascular coupling in DME. Methods The differential expression analysis, STEM, and WGCNA were performed from GSE160306 to identify hub genes. The gene expression was validated by RT-qPCR. The relevant mechanisms of action were investigated through GO, KEGG, and GSEA analyses, as well as co-expression networks. Additionally, the LASSO regression analysis and a nomogram were used to demonstrate the diagnostic effectiveness of the model. Finally, the GenDoma platform was utilized to identify drugs with potential therapeutic effects on DME. Results Neurotrophic factor receptor (NGFR) was identified as a hub gene related to neurovascular coupling and DME. The expression of NGFR was verified by RT-qPCR in vitro cells. GSEA analysis indicated that high expression of NGFR may affect immunity and inflammatory pathway, thereby regulating neurovascular coupling and mediating the development of DME. The NGFR co-expression network was constructed, which exhibited the correlation with the neurotrophin signaling pathway. Moreover, a diagnostic model for DME based on NGFR and PREX1 demonstrated relatively good diagnostic performance using LASSO regression analysis and the nomogram. And then the GenDoma platform identified drugs with potential therapeutic effects on DME. Conclusion The high expression of NGFR may lead to abnormal neurovascular coupling and participate in the occurrence of DME by regulating the immunity, inflammatory and neurotrophin signaling pathway. Detection of NGFR and related expression genes may be beneficial for monitoring the occurrence and development of DME.